Peran Tokoh Agama Mencegah Kenakalan Remaja di Desa Onan Lama Kab. Dairi - Mulak Ate Lingga; Sakti Ritonga; Ismail Ismail (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research wants to see how religious figures play a role in cases or control the actions of teenagers who are considered to violate the values ​​of decency, propriety and various kinds in the village of Onan Lama, Dairi Regency. The method used is qualitative research. The research location was carried out in Onan Lama Village, Dairi Regency, Sidikalang City. In this case, to obtain the data in question, researchers carried out observations, interviews and documentation. The techniques used in data analysis are data collection, data reduction, data presentation and drawing conclusions. The results of this research show that religious leaders carry out their role in preventing juvenile delinquency in Onan Lama Village through several activities such as: (1) religious activities (2) alcohol and drug education (3) discussions and collaboration with parents. Furthermore, Onan Lama Village religious leaders carry out social control to prevent juvenile delinquency by: (1) approaching individuals (2) participating in religious activities (3) religious practices